Reconsideration of the Adsorption/Desorption Characteristics with the Influences of Water in Unconventional Gas Systems - Yunchao Pu; Yanchun Wang; Juntai Shi; Keliu Wu (Geofluids)
The exploration and development of unconventional resources have been of growing interest in the industry in recent years. It is widely known that the adsorption and desorption mechanisms of unconventional gas have great significance for gas accumulation and exploration. However, major researches based on the mechanism of solid-gas interface have failed to reveal it completely, which introduce large discrepancies between actual and predicted production. In this paper, the mechanism of solid-liquid-gas adsorption and desorption interface is enlightened to describe the characteristics of unconventional gas. The validity of the proposal was verified preliminarily by building a conceptual model which redefines the gas-water distribution. Furthermore, the possibility of production of gas trapped in micropores was first investigated. The findings of this study can help for better understanding of the adsorption, desorption, and production mechanisms and in unconventional gas system. Accordingly, the explanation of variation between experiment result and actual production rate even with physical parameters was reasonable in theory. Therefore, this work should provide a basis for improving the accuracy of production predictions in actual reservoirs and should assist analysts in determining reasonable unconventional gas target.